1991
DOI: 10.1016/0035-9203(91)90177-z
|View full text |Cite
|
Sign up to set email alerts
|

Minor role of hepatitis B virus in the causation of chronic liver disease in Somalia indicated by a case-control study

Abstract: Chronic liver disease (CLD) is frequent in Somalia. In a case-control study, 116 in-patients with CLD were compared with the same number of age and sex matched controls. Demographic variables, use of drugs, symptoms and signs, serological markers for hepatitis B virus (HBV) and serum alpha-foetoprotein (AFP) were assessed. Hepatitis B surface antigen (HBsAg) was found in 44 cases of which 17 had antibodies to hepatitis D virus (anti-HD) and 7 had hepatitis B e antigen (HBeAg). Twenty-three controls were HBsAg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In 1989, a total of 1138 subjects with HBsAg were examined from different regions of Somalia; the results showed that 19.3% (220/1138) of subjects were HBsAg-reactive[ 31 ]. Bile KM and his colleagues conducted a case-control study that detected that 28.8% (67/232) of the overall prevalence was HBsAg subjects, including cases and control groups[ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1989, a total of 1138 subjects with HBsAg were examined from different regions of Somalia; the results showed that 19.3% (220/1138) of subjects were HBsAg-reactive[ 31 ]. Bile KM and his colleagues conducted a case-control study that detected that 28.8% (67/232) of the overall prevalence was HBsAg subjects, including cases and control groups[ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies met the inclusion criteria for the meta-analysis of the prevalence of HBV infection among patients with chronic liver disease, including patients with hepatocellular carcinoma, in Somali people. Their prevalence ranges from 17.9% to 50%[ 30 , 32 , 34 , 36 - 38 ] (Table 6 ). The pooled effect size for the prevalence of hepatitis B among chronic liver disease patients in Somali people was 39.2% (95%CI: 33.4% to 45.4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the 62 (5, 87-143) studies to be included were identified assessing the HDV prevalence in the EMRO countries and fulfilling inclusion criteria. Out of these,19 studies (95-113) were in Iran, nine studies (129-137) in Saudi Arabia, seven studies (5, 119-124) in Pakistan, six studies (89-94) in Egypt, four studies (138-141) in Tunisia and Somalia (125-128) and two studies (142, 143) in Yemen. There was one study of other countries which consisted of: Afghanistan (87), Djibouti (88), Jordan (114), Kuwait (115), Lebanon (116), Morocco (117), and Oman (118).…”
Section: Resultsmentioning
confidence: 99%
“…HBV infection is highly endemic in many developing countries, including those in Asia, Africa and the Western Pacific (Hawkes et al, 1981;Hyams et al, 1989;Boutin et al, 1990;Bile et al, 1991;Tan et al, 1991) . In such a setting, most persons are infected in early childhood though both perinatal transmission (mother to infant at birth) and horizontal transmission (close contact with other infected persons) .…”
Section: Introductionmentioning
confidence: 99%